2023
DOI: 10.1186/s12882-022-03031-y
|View full text |Cite
|
Sign up to set email alerts
|

Does acute kidney injury alerting improve patient outcomes?

Abstract: Background Electronic alerts (e-alerts) for Acute Kidney Injury (AKI) have been implemented into a variety of different Electronic Health Records (EHR) systems worldwide in order to improve recognition and encourage early appropriate management of AKI. We were interested in the impact on patient safety, specialist referral and clinical management. Methods All patients admitted to our institution with AKI were included in the study. We studied AKI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Educational interventions at teaching hospitals in the UK, designed to increase understanding of AKI, demonstrated increased physician awareness based on self-reported management of patients and comparison of AKI knowledge assessed on pre- and post-education questionnaires [ 12 ]. In another UK study, electronic alerts deployed at a teaching hospital not only raised awareness of AKI but improved outcomes, leading to less progression to higher stages of AKI, fewer emergency re-admissions, and a reduction in mortality [ 13 ]. A pediatric multi-center intervention to raise awareness of the impact of nephrotoxic medications on the development of AKI led to decreased AKI rates [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Educational interventions at teaching hospitals in the UK, designed to increase understanding of AKI, demonstrated increased physician awareness based on self-reported management of patients and comparison of AKI knowledge assessed on pre- and post-education questionnaires [ 12 ]. In another UK study, electronic alerts deployed at a teaching hospital not only raised awareness of AKI but improved outcomes, leading to less progression to higher stages of AKI, fewer emergency re-admissions, and a reduction in mortality [ 13 ]. A pediatric multi-center intervention to raise awareness of the impact of nephrotoxic medications on the development of AKI led to decreased AKI rates [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the development of AKI was similar in those categorized as low versus medium/high risk based on TIMP2ÃIGFBP7 levels (30.4 and 32.9%). There have been other recent reports of single-centre implementation of eAlerts [19], although the level of evidence generated from before-after comparisons (that cannot eliminate temporal trends that occur independently to the intervention) is less robust that that derived from randomised trials.…”
Section: Key Pointsmentioning
confidence: 97%
“…Electronic alerts in the hospitals were recommended to improve the recognition of AKI, and an AKI electronic alert system was mandated by NHS England in all Laboratory Information Management Systems across the NHS in 2015 [5]. Several trials focusing on patient safety, specialist referral, and clinical management showed positive effects of AKI electronic alert systems, including more frequent medication-related recommendations per patient, a reduced progression to higher AKI stage, emergency readmission to hospital, reduced length of stay in hospital and death during admission [6][7][8], see Appendix A, Table A1. A pragmatic stepped wedge cluster randomized trial showed improved AKI recognition, increased care, and shorter length of hospital stay in the intervention group but did not reduce 30-day AKI mortality [9].…”
Section: Introductionmentioning
confidence: 99%